Evaluation of body mass index in patients with dipper and non-dipper hypertension - Memioğlu, Tolga; İnanır, Mehmet; Argana, Kıvanç; Kiriş, Salih Vahit; Güven, İbrahim; Dıramalı, Murat; Toprak, Kenan; Özyaşar, Mehmet (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCircadian variation in blood pressure, particularly the distinction between dipper and non-dipper profiles, plays a critical role in cardiovascular risk stratification. Although recent studies suggest that obesity may contribute to non-dipping patterns, the relationship remains controversial.ObjectiveTo compare body mass index (BMI) between dipper and non-dipper hypertensive patients and to evaluate whether BMI can serve as a marker of non-dipping status.MethodsThis retrospective observational study analyzed ambulatory blood pressure monitoring (ABPM) records of 200 patients (100 dippers and 100 non-dippers) who underwent 24-h ABPM using a validated Holter device. BMI values were calculated and compared between groups.ResultsThe distribution of sex did not differ significantly between dipper and non-dipper patients (p = 0.571). The mean BMI was significantly higher in the non-dipper group compared with the dipper group (30.75 ± 5.42 vs. 28.07 ± 5.09 kg/m2, p = 0.002). Non-dipper hypertensive patients demonstrated significantly higher BMI levels than dipper patients.ConclusionsThese findings support the hypothesis that obesity may impair nocturnal blood pressure regulation and suggest that BMI could serve as a simple marker of non-dipping status. This indicates a potential association between increased BMI and a non-dipping blood pressure profile. Due to its retrospective design, this study cannot establish causality.